RESILIENCE AS MEDIATOR FACTORS AMONG PEOPLE WITH NON SUBSTANCE USE DISORDER AND SUBSTANCE USE DISORDER - Mughal, Huma; Akhwanzada , Wajid Ali; Azeemi, Mian Mukhtar Ul Haq; Abbas, Amer; Khan, Darya; Khan, Jaffar (Khyber Journal of Medical Sciences, 2022)
Objective: To find out resilience as protective factor among people with substance use disorder and non-substance use group. Methods: This is a cross sectional study design, in which data was collected from Hayatabad Medical complex (HMC), Lady reading hospital (LRH) Khyber teaching hospital (KTH) and other rehab centers. Ethical approval was obtained from research ethical committee. Total (N=50) participants were selected through purposive sampling. Participants were divided into 2 groups, one group consisted of (n=25) drug addicted participants whereas, another group consisted of (n=25) non drug addicts. Data was measured on Cannon-Davidson scale and Drug screening test. For analysis of data t test was used to make comparison between two groups. Results: In the present study the mean of drug abuse group (m=14.04) with p> =.05 values whereas non-drug abuse (m=31.96) on resilience scale. Results reveals a significant difference between drug abuse group (m=8.28) and non-drug abuse (m=.72) on p>=.05 level of confidence interval on drug screening test. Conclusion: This study shows that individuals with higher resilience has less problems with substance use, on the other hand individuals with less resilience has more problems with substance use. Key words: Resilience, Protective factors, Substance use disorders, Non substance use disorder